Le rôle du Canada dans le développement du droit en matière de conflit armé - Green, Leslie (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
This paper is concerned with examining the role Canada has played in the development of the law of armed conflict. It makes the point that, while it is generally assumed that the Canadian courts followed the practice of those in the United Kingdom, this is too simple an approach. From the early years of the nineteenth century, the Vice-Admiralty Court in Halifax was making a contribution to the law of prize and maritime war law that might be compared with that of Lord Stowell in England. Moreover, even then, it was applying principles that have only recently been generally accepted — that armed conflict is as much a question of fact as of law, and that naval officers, at least, must be taken to know the law. It is hardly believable that as long ago as 1814, Dr. Croke was upholding the immunity from capture of "the arts and sciences... as the property of mankind at large, and as belonging to the common interests of the whole species. " In addition to these early decisions in maritime war law, the Canadian courts have stood almost alone in the English-speaking world in explaining the criminal liability of escaping prisoners of war, in terms which to some extent formed the basis of what appeared in the Geneva Convention of 1949. At the same time, a Canadian war crimes tribunal made an important contribution to the exposition of the nature of a commander's liability for the offences of his subordinates, while others added to the jurisprudence concerned with the nature of the defence of superior orders. In so far as an actual innovative contribution is concerned, it must not be forgotten that the enunciation by Daniel Webster in 1842 of the concept of self-defence as understood in international law resulted from the actions of loyalists during the 1837 Rebellion. More recently, Canada played a concrete role in the drafting of the 1977 Protocols additional to the 1949 Geneva Conventions for the development of humanitarian law in armed conflict. In fact, Protocol II relating to non-international conflict is almost entirely based on a Canadian draft expressing Canada*s concern to see principles of humanitarian law observed as widely as possible, regardless of the nature of the conflict. As a result of tracing Canada 's role one is led to the conclusion that itconstitutes a record of achievement that merits wider appreciation.